Paroxysmal Nonepileptic Spells in Adolescence - Willis, Erin; Samanta, Debopam (Journal of Pediatric Epilepsy, 2015)
Paroxysmal nonepileptic spells refer to events that clinically can resemble epileptic seizures but are not caused by abnormal epileptiform activity in the brain. These spells can often be difficult to diagnose owing to clinical similarities, but a correct diagnosis is needed to prevent unnecessary treatment with antiepileptic drugs. We review the most common diagnoses in adolescents that can be mistaken for epilepsy, including migraine, syncope, movement disorders, sleep disorders, and psychologic disorders.
Keywords: paroxysmal nonepileptic; spells; psychogenic seizures